2000
DOI: 10.1074/jbc.m003893200
|View full text |Cite
|
Sign up to set email alerts
|

31P NMR Spectroscopy of Trypanosoma brucei, Trypanosoma cruzi, and Leishmania major

Abstract: High resolution31 P nuclear magnetic resonance spectra at 303.6 MHz (corresponding to a 1 H resonance frequency of 750 MHz) have been obtained of perchloric acid extracts of Trypanosoma brucei, Trypanosoma cruzi, and Leishmania major, the causative agents of African sleeping sickness, Chagas' disease, and leishmaniasis. Essentially complete assignments have been made based on chemical shifts and by direct addition of authentic reference compounds. The results indicate the presence of high levels of short chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
82
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 57 publications
5
82
0
Order By: Relevance
“…Poly P is a linear chain of a few to many hundreds of phosphate (P i ) residues linked by high-energy phosphoanhydride bonds [8]. T. cruzi is especially rich in short chain poly P such as poly P 3 , poly P 4 , and poly P 5 [9]. 31 P NMR spectra of purified acidocalcisomes of T. cruzi indicated that the poly P has an average chain length of 3.25 phosphates [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly P is a linear chain of a few to many hundreds of phosphate (P i ) residues linked by high-energy phosphoanhydride bonds [8]. T. cruzi is especially rich in short chain poly P such as poly P 3 , poly P 4 , and poly P 5 [9]. 31 P NMR spectra of purified acidocalcisomes of T. cruzi indicated that the poly P has an average chain length of 3.25 phosphates [9].…”
Section: Introductionmentioning
confidence: 99%
“…T. cruzi is especially rich in short chain poly P such as poly P 3 , poly P 4 , and poly P 5 [9]. 31 P NMR spectra of purified acidocalcisomes of T. cruzi indicated that the poly P has an average chain length of 3.25 phosphates [9]. Based on the total concentration of poly Ps in different stages of T. cruzi, the relative volume of the acidocalcisomes in these cells (0.86%, 2.3%, and 0.26% of the total cell volume of epimastigotes, amastigotes and trypomastigotes, respectively; ref.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the relation between polyP metabolism and its cellular role, studies were performed on the polyP composition and on the characterization of enzymes involved in the metabolism of these compounds. Short-and long-chain polyP and PP i were shown to be present in the acidocalcisomes of T. brucei bloodstream forms (BF) (12,13). The turnover of the acidocalcisome PP i pool is low (14), suggesting that PP i could be a product of polyP metabolism.…”
mentioning
confidence: 96%
“…Moreno et al (12) have reported that short-chain polyP of an average chain length of 3.3 phosphates and PP i are the most abundant phosphorus-containing compounds in acidocalcisomes. The short-chain polyP concentration in T. brucei PF has been previously reported to be around 50 mM (9).…”
Section: Role Of the N-terminal Extension In The Oligomerization Andmentioning
confidence: 99%
“…Two exceptions are the bloodstream forms of T. cruzi (Correa et al 2002) and the culture forms of Phytomonas françai (Miranda et al 2004) that have been shown to contain iron-rich acidocalcisomes. 31 P NMR and biochemical analysis have shown that the phosphorus present in these organelles is primarily in the form of pyrophosphate, and short and long chain polyphosphate (Urbina et al 1999, Moreno et al 2000, Ruiz et al 2001b.…”
Section: Introductionmentioning
confidence: 99%